Synthesis of Two Steroids Derivatives and its Relationship with some Physicochemical Parameters - Lauro Figueroa-Valverde; Francisco Díaz-Cedillo; Elodia Garcia-Cervera (E-Journal of Chemistry)
Two danazol derivatives were synthesized and characterized by spectral analyses. In order to characterize the structural and physicochemical requirements of danazol derivatives, several parameters such HOMO-LUMO gap, ΔHf, RMSg, dipole moment (µ) and bond length were evaluated. The results showed that HOMO and µ was high in the compound 5 in comparison with the compound 3. In conclusion all these data indicate that increase in the length of chain induce greater moment dipole and increase HOMO gap in the compound 5 with respect to 3.